2013
DOI: 10.1245/s10434-012-2791-7
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Cytoreductive Surgery for Appendiceal Carcinomatosis: Morbidity, Mortality, and Survival

Abstract: Background Cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemoperfusion (HIPEC) are frequently used to treat appendiceal carcinomatosis. Some patients require multivisceral resection because of the volume of disease. It is unclear whether extent of CRS impacts survival in appendiceal carcinomatosis. Methods We analyzed 282 patients undergoing attempted CRS/HIPEC for appendiceal carcinomatosis. Patients were defined as having undergone Extensive CRS (n = 60) if they had >3 organ resections or >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 31 publications
2
32
1
Order By: Relevance
“…Moreover, we found a correlation between multi-organ resection and higher incidence of perioperative morbidity by univariate analysis, contrary to the findings in previous similar studies [15,16]. Overall and major morbidity rates (74% and 34% respectively) in the extreme group were significantly higher, but still comparable to those reported by Gusani and colleagues, who compared morbidity outcomes from 15 centers and reported overall and major morbidity rates of 30e74.2% and 12e66%, respectively [21].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Moreover, we found a correlation between multi-organ resection and higher incidence of perioperative morbidity by univariate analysis, contrary to the findings in previous similar studies [15,16]. Overall and major morbidity rates (74% and 34% respectively) in the extreme group were significantly higher, but still comparable to those reported by Gusani and colleagues, who compared morbidity outcomes from 15 centers and reported overall and major morbidity rates of 30e74.2% and 12e66%, respectively [21].…”
Section: Discussioncontrasting
confidence: 99%
“…Similar to the results of another study that examined the effect of extensive CRS/HIPEC procedures in patients with appendiceal neoplasms [16], our findings demonstrate that extreme CRS/HIPEC procedures are associated with longer duration of surgery, longer hospital stay and increased blood transfusion requirements. Moreover, we found a correlation between multi-organ resection and higher incidence of perioperative morbidity by univariate analysis, contrary to the findings in previous similar studies [15,16].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The main goal of PMP treatment is the prevention of locoregional recurrence rather than systemic disease. Wagner et al [22] retrospectively analysed 282 patients undergoing CRS and HIPEC. They concluded that the extent of CRS does not affect the morbidity but prolongs the survival [22].…”
Section: Discussionmentioning
confidence: 99%
“…Wagner et al [22] retrospectively analysed 282 patients undergoing CRS and HIPEC. They concluded that the extent of CRS does not affect the morbidity but prolongs the survival [22]. Recently a large multicentre retrospective study by Chua et al [23] with more than 2,000 patients with PMP was published.…”
Section: Discussionmentioning
confidence: 99%